Leadership in recreation - RUSSELL, Ruth V (McGraw - Hill Book Company, 2005)
This is primarily a text for undergraduate students preparing for careers in the management of recreation settings. Coverage includes the concepts and skills required to conduct recreational activities and to supervise volunteer and paid staff in recreation agencies and organisations. It can be used for a course on recreation leadership, recreation supervision, or recreation activity methods, and because of its comprehensiveness, the book is also useful as a resource for practising recreation professionals. Examples are drawn widely from outdoor recreation, therapeutic recreation, sport and fitness, adventure settings, municipal services, and hospitality and tourism.